Identity Recognition Using an Artificial Intelligence Based on Artificial Immune System - Da Silva, Jadiel Caparrós [UNESP]; Lima, Fernando Parra Dos Anjos [UNESP]; Lotufo, Anna Diva Plasencia [UNESP]; Batista, Jorge Manuel Moreira De Campos Pereira (Institute of Electrical and Electronics Engineers (IEEE), 2015)
This work aims to realize identity recognition using images from one Database [1]. This facial database is composed of 3D dynamical images or 4D considering the time component as the fourth dimension, where the head movements are removed and only the facial dynamism is considered. The identity recognition is done by an Artificial Intelligence method based on Artificial Immune System of Negative Selection. The performance of the Immune system is satisfactory and encouraging. The obtained results are efficient, robust, precise and reliable to recognize the facial identity.
Keywords: artificial immune system of negative selection; artificial intelligence; detection and classification; identity recognition